Clinician perception of care at the end of life in a quaternary neonatal intensive care unit - Imai, Lauren; Gray, Megan M.; Kim, Brennan J. H.; Lyle, Allison N. J.; Bock, Amber; Weiss, Elliott Mark (Frontiers in Pediatrics, 2023)
Care for neonates at the end of life (EOL) is often challenging for families and medical teams alike, performed suboptimally, and requires an experienced and compassionate clinician. Much literature exists on adult and pediatric EOL care, but limited studies examine the neonatal process. We aimed to describe clinicians' experiences around EOL care in a single quaternary neonatal intensive care unit as we implemented a standard guideline using the Pediatric Intensive Care Unit-Quality of Dying and Death 20 tool. Surveys were completed by 205 multidisciplinary clinicians over three time periods and included 18 infants at EOL. While most responses were high, a meaningful minority were below goal (<8 on 0-10 scale) for troubling symptom management, conflict between parents and staff, family access to resources, and parent preparation of symptoms. Comparison between Epochs revealed improvement in one symptom management and four communication categories. Satisfaction scores related to education around EOL were better in later Epochs. Neonatal Pain, Agitation, and Sedation Scale scores were low, with few outliers. These findings can guide those aiming to improve processes around neonatal EOL by identifying areas with the greatest challenges (e.g., conflict management) and areas that need further study (e.g., pain management around death).